Escapism as a Predictor of Revisit Intention through Attitude Toward Behavior - Fitria Noviyanti; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the influence of scenery and escapism on the revisit intention of tourists at Pangandaran Beach through attitude toward behavior, subjective norms, and perceived behavioral control. This study used a survey method involving 155 respondents who had experience visiting Pangandaran Beach. The data analysis technique used was structural equation modeling (SEM) using smartPLS software version 3.0. Based on the results of the hypothesis testing, it was found that escapism had a positive effect on revisit intention through attitude toward behavior. The novelty of this study is the addition of the escapism variable, which is hypothesized to have a positive effect on revisit intention. The researchers hope that the findings obtained can contribute to future researchers and Pangandaran Beach managers in designing strategies that can increase tourist revisit intention. Future researchers can consider exploring other factors suspected of being able to predict revisit intention.